HLA ANTIGENS OF ARAB CHRISTIANS IN IRAQ - Mahdi, Batool M.; Moussawy, khalida M.; Al-shaikhly, Abdul wahab A.R.; Ad;’haib, Ali H. (Journal of the Faculty of Medicine Baghdad, 2005)
BACKGROUND: Iraq had more than twenty-four millions inhabitants of populations. This nation is one of the most populated countries in the world. It is difficult to define Iraqi populations genetically (HLA polymorphism) because they are structured of a mixture of many groups. HLA phenotype frequencies that encoded by many closely linked genes that are responsible for a variety of cell surface alloantigen proteins that are responsible for differences in different ethnic groups. Arab Christians in Iraq, accounting for more than three millions inhabitant mostly the northwest and other parts of Iraq. This raised the need for a preliminary study of the HLA trend in this population. Aim of study: 1- Estimating the gene frequency of HLA class I (A, B, Cw) and class II (DR and DQ) alleles in Iraqi Arab Christians. 2- Assessing the genetic relationship between Iraqi Arab Christians and other Arabian, Asian and European populations. Materials and Methods: A total of unrelated 568 Iraqi Arab Christians (AC) healthy volunteers and individuals referred to Immunology and Tissue Typing Center in Al- Karamah Teaching Hospital for organ transplantation and Forensic medicine) were examined for HLA polymorphism using complement dependent cytotoxicity test from June-2003 to April-2004. Results and conclusions: The phenotypes of all loci of (AC) were in agreement with Hardy-Weinberg equilibrium. In case of HLA-A locus, three variants dominate this locus Al(0.123), A2 (0.149) and A3(0.134) which showed some similarities with Arabian , Asian and European people in the world. A3 had been found to be associated with Hereditary Hemochromatosis (HH) but the risk increased when there is a linkage disequilibrium between A3/B14. Fortunately, BI4 allele had a low frequency in this group and common allele was B35(0.154) and 851(0.128) which had an association with Behqet ’s syndrom. So one can predict high incidence of this disease in this group of population. Last locus was studied in class I was Cw4 that had a higher rate (0.173) in HLA -Cw loci. In case of class II, it was done on small number of persons and the common allele was DR2(53.84%) which is protective from insulin dependent diabetes mellitus disease while DQ1 is common allele in HLA-DQ loci. HLA typing of (AC) had some similarity with Arabian people because of their same ancestry and also had some similarity with Caucasoid Europeans because of outbreading and intermixing with those populations due to migration.